Pengaruh Pengembangan Karir dan Work Life Balance terhadap Turnover Intention dengan Retensi Karyawan sebagai Variabel Mediasi - Putri, Indira Natasya Kusuma; Yulihasri; Games, Donard (Jurnal Informatika Ekonomi Bisnis, 2024)
In the era of competitive business and Industry 5.0, human resource management (HRM) becomes crucial for achieving competitive advantage through the development, reinforcement, and transformation of organizational culture. This study explores the influence of career development and work-life balance on the turnover intention of female employees at Bank Nagari. Employees are considered the most important assets because their contributions affect the company's reputation and profitability. The involvement of female workers provides valuable skills, diversity, and inclusivity, yet their representation in leadership roles remains low. This research uses a quantitative method with primary data collected through questionnaires from 67 female employees at Bank Nagari headquarters. The results show that career development does not significantly affect turnover intention, while work-life balance has a significantly negative influence on the intention to leave. Demographic factors such as age, marital status, length of service, and income level play a more dominant role in influencing employees' decisions to stay. Additionally, employee retention and job satisfaction act as mediators in the relationship between work-life balance and turnover intention, indicating that policies supporting work-life balance and effective career development programs can enhance retention and reduce turnover intention. Investing in career development programs and work-life balance is a crucial strategy for increasing employee satisfaction and loyalty.